B-Spline Solution for a Convection-Diffusion Equation - Çağlar, Süleyman Hikmet; Çağlar, Hatice Nazan; Özer, Mehmet (Polish Acad Sciences Inst Physics, Al Lotnikow 32-46, Pl-02-668 Warsaw, Poland, 2014)
This paper is concerned with the numerical solution of the convection diffusion problems. A family of B-spline methods has been considered for the numerical solution of the problems. The results showed that the present method is an applicable technique and approximates the exact solution.